430 PLATELET ACTIVATING FACTOR INDUCES DE NOVO SYNTHESIS OF INFLAMMATORY PROTEINS BY HUMAN POLYMORPHONUCLEAR LEUKOCYTES ISOLATED FROM TERM CORD BLOOD. (1st January 2005) - Rubner, F.; Zimmerman, G.; Weyrich, A.; Yost, C.
Abstract : Background: Many neonatal diseases are regulated by inflammation. This process is intricate and is balanced by pro- and anti-inflammatory arms. Polymorphonuclear leukocytes (PMNs) are key inflammatory mediators because they are one of the first responders in microbial invasion and tissue injury. It is generally believed that PMNs control inflammation through rapid degranulation and release of preformed constituents. However, we have recently demonstrated that PMNs isolated from adults alter their phenotypic make-up by synthesizing new inflammatory proteins. Here, we determine if PMNs from term newborns have similar inflammatory potential. Methods: PMNs were directly isolated from term, umbilical human whole blood by positive selection of CD15+ cells rather than standard Ficoll-Paque procedures. The cells were subsequently stimulated with platelet activating factor (PAF), a potent cellular agonist that is generated during neonatal inflammation. Interleukin-6 receptor alpha (IL-6Rα), IL-8, and retinoic acid receptor alpha (RARα) gene expression in PMNs was determined. Results: With equivalent starting material, whole blood isolation of PMNs yielded a more homogeneous cell population and significantly greater number of PMNs (over 3-fold) compared to Ficoll-Paque procedures. Moreover, isolation time was reduced by 2 hours and basal protein expression was non-existent in PMNs from whole blood isolates. PAF markedly increased COX-2, IL-6Rα, IL-8, and RARα protein production in term PMNs, paralleling responses that we have previously seen in adult PMNs. Conclusions: These results demonstrate that PMNs isolated from term newborns are capable of synthesizing new inflammatory protein products, consistent with the ability of term newborns to generate a "mature" inflammatory response to stave off infection. We predict that gene expression profiles will differ in pre-term PMNs where dysregulated inflammation is more prevalent.